PENERAPAN KODE ETIK ATAS ETIKA PROFESI HUKUM PADA PROFESI NOTARIS - Ahmad Syarif Hidayatulloh; Dimas Maulana Jaka Perdana; M.Farhan Adzkiya; Jefri Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research will discuss the notary professional code of ethics. A professional code of ethics is a norm established and accepted by a professional group, which directs or gives instructions to its members on how they should act and at the same time guarantees the moral/ethical quality of the profession in the eyes of the public. A notary, which is one of the legal professions, is required to have a good personality. As a public official, a notary is required to have a personal ethic, one of which is the spirit of Pancasila, obeying the laws and regulations in force in the Republic of Indonesia. The notarial profession is so crucial and noble that when carrying out their position a notary must comply with the applicable regulations, including using an office that has been determined by law, being aware of their obligations, not using mass media, and putting up nameplates in accordance with the provisions. The importance of this is because the presence of a notary will be needed by the community in the process of resolving the cases they experience, especially in the field of authentic deeds.